Class matters: A study of minority and majority social mobility in Britain, 1982–2011 - Li, Y; Heath, A (University of Chicago Press, 2016)
This article asks whether standard accounts of class reproduction apply among migrants and their descendants as among the majority group, whether there is a process of assimilation across generations toward the overall (British) pattern of class reproduction, whether the trends over time in absolute and relative mobility among the majority population are mirrored among migrants and their descendants, and whether trends in class reproduction are mirrored in trends in ethnic stratification. Using national representative surveys covering four decades, the authors find a major generational shift, with the first generation experiencing a notable social decline but the second generation having a clear advancement. Relative mobility rates among migrants and their descendants are close to those of the majority group and exhibit similar trends over time. Ethnic stratification also appears to be slowly declining, although the persistence of unemployment among the second generation qualifies the optimistic story of ethnic socioeconomic assimilation.